IMPLEMENTASI ACCESS CONTROL LIST DALAM PERANCANGAN VIRTUAL LOCAL AREA NETWORK PADA PT CAKRAMEDIA INDOCYBER - Fahrizal Fahrizal; Bayu Arikha Candra (Institut Teknologi dan Bisnis Swadharma, 2022)
The limited network resources make the company network managers have to act more wisely in the use of these resources, one of which is by limiting the use of resources and prioritizing their use only for the company's main interests. Implementing a Virtual Local Area Network (VLAN) and switch port security can be done to limit user access between networks in the company and to implement access role's, router access list's (ACL's) are applied so that the network only forwards permitted data based on the company's communication needs. The ACL's router used in this study uses the ACL's standard because it is not yet known the specific needs for TCP and UDP data restrictions in the company. The results of this implementation are expected to improve the security and effectiveness of network use at the PT. Chakramedia Indocyber. The method used in this research is to use the observation method and the interview method to get to the problems that exist in the company and analyze the availability and needs of network hardware. As well as using laboratory research to get a suitable configuration solution.